Search and multiple jobholding - Etienne Lalé (W.E. Upjohn Institute for Employment Research, 2019)
A search-theoretic model of the labor market with idiosyncratic fluctuations in hours worked, search both off- and on-the-job, and multiple jobholding is developed. Taking on a second job entails a commitment to hold onto the primary employer, enabling the worker to use the primary job as her outside option to bargain with the secondary employer. The model performs well at explaining multiple jobholding inflows and outflows, and it is informative for understanding the secular decline in multiple jobholding. While some worry that this decline heralds a less-flexible labor market, the model reveals that it has contributed to reducing search frictions.
Keywords: E24; J21; J62; 330; Multiple jobholding; Employment; Hours worked; Job search